Efficient signed-digit-to-canonical-signed-digit recoding circuits. (November 2016) - Tanaka, Yuuki
Abstract: In this study, we propose a new signed-digit-to-canonical-signed-digit recoding circuit based on parallel prefix structures. Several articles have been devoted to the study of canonical signed-digit recoding circuits. However, most of those re-code from 2's complement binary number representation. Unlike those, our proposed architectures convert from signed-digit number representation. The circuit structure is somewhat different from those in previous articles, because each digit in the input is accompanied by its sign. We evaluate the proposed circuit and compare it with a circuit based on the conditional sum structure. We show that the proposed architectures performs faster by 30% or more than the circuit based on the conditional sum structure.